Preparation and Characterization of Binahong (Anredera cordifolia) Leaf Extract Transfersome Wound-Healing Gel - Immanuel, Handika; Yuliani, Sri Hartati; Dwiastuti, Rini; Nugraha, Alvin Arya; Limianty, Angela; Annabel, Evangeline Keisha; Lu, Felisha; Lestari, Fajar Sri; Branitasandini, Regina Epiphania (Sanata Dharma University, 2024)
Burn injuries are a significant global health concern due to their profound impact on morbidity and mortality rates. Immediate medical care is essential given the potential for bacterial infections to complicated burn injuries. Binahong leaves (Anredera cordifolia (Ten.) Steenis) contain vitexin compounds that demonstrate wound healing and antibacterial potential. However, vitexin has low solubility, prompting the use of ethanol for extraction and the introduction of nanoparticle technology to enhance solubility, namely transfersomes. The present study explored the development of a gel using binahong extract transfersomes with the composition of carbopol 940 and Na-CMC to determine the effect of carbopol 940, Na-CMC, and the interaction of the two on the gel’s physical properties and stability as well as obtain the optimum composition of the two. This study demonstrates positive results in terms of gel physical properties, including pH, spreadability, and viscosity. A Factorial design method is used for optimization. The results showed that Na-CMC had the most effect on increasing viscosity, while carbopol 940 had the most effect on reducing spreadability. The optimal formula obtained in this research was to use 0.653 grams of Na-CMC and 4.391 grams of Carbopol as gelling agents.